The wind and the sun - De Paola, Tomie; Aesop (Parsippany, NJ : Silver Press, 1995)
The sun and the wind test their strength by seeing which of them can force a man to remove his cape.
Based on a fable by Aesop.
1.7
K-3
Keywords: Fables; Fables